Electrical and optical properties of ZnO-milled Fe2O3 nanocomposites produced by powder metallurgy route - Güler, Seval Hale; Güler, Ömer; Evin, Ertan; Islak, Serkan (Elsevier BV, 2016)
Abstract In this study, ZnO–Fe 2 O 3 nanocomposites were synthesized by powder metallurgy route and characterized through X-ray diffraction, UV–vis diffuse reflectance spectroscopy, scanning electron microscopy, electrical conductivity measurement device. The amount of Fe 2 O 3 in the ZnO and milling time were varied in order to investigate their influence on the electrical and optical properties of the samples. Powder mixture containing milled and unmilled Fe 2 O 3 at the rates of the 1, 3 and 5 wt% was sintered in vacuum environment. Results show that the conductivities of ZnO–Fe 2 O 3 nanocomposites slightly increased by increasing the Fe 2 O 3 content and these composites have potential materials for photocatalysis. Besides, electrical and optical properties of ZnO–Fe 2 O 3 nanocomposites varied according to status of unmilled Fe 2 O 3 and milled Fe 2 O 3 .